Evangelical News : Politics, Gender, and Bioethics in Conservative Christian Magazines of the 1970s and 1980s - Bassimir, Anja-Maria (Book collections on Project MUSE., 2022)
"This work is an innovative treatise on the evangelical magazine market during the 1970s and 1980s and how it sustained religious community and ideology. Bassimir argues that community can be produced in discourse, especially when shared rhetoric, concepts, and perspectives signal belonging. The 1970s and 1980s were a tumultuous period in United States history. In suit with a dramatic political shift to the right, evangelicalism also entered the public discourse as a distinct religious movement and was immediately besieged by cultural appropriations and internal fragmentations. This was also a time when Americans in general and evangelicals in particular grappled with issues and ideas such as feminism and legal abortion, restructuring traditional roles for women and the family. The Watergate Crisis and the newly emerging Christian Right also threw politics into turmoil. During this time, there was a surge of readership for evangelical magazines such as Christian Today, Moody Monthly, Eternity, and Post-Americans/Sojourners. While each of these magazines-and many other publications-contributes to and participates in the overall dissemination of evangelical ideology, they all also have their own outlooks and political leanings when it comes to hot-button issues. Evangelical Visions, through a thoroughly researched lens, makes important correctives to common understandings of evangelical discourse, particularly regarding the key political initiatives of the religious right. Bassimir demonstrates that within the pages of these periodicals, evangelicals hashed out a number of competing views on feminism, abortion, reproductive technologies, and political involvement itself. To accomplish this, Evangelical Visions traces the emergence of evangelical social and political awareness in the 1970s to the height of its power as a political program. The chapters in this monograph also delve into such topics as how evangelicals re-envisioned gender norms and relations in light of the feminist movement and the use of childhood as a symbol of unspoiled innocence and the pure potential of humanity. Presently, most accounts of evangelicalism cite evangelical magazines only very selectively, and virtually no studies make substantive use of those magazines as objects of investigation. Bassimir's Evangelical Visions makes a much needed contribution to our understanding of evangelicalism in the late twentieth century by providing a nuanced picture of a religious subculture that is too often reduced to caricature. This study is located at the intersection of history, religious studies, and media studies and will appeal to scholars and students of all of these fields"--